2014
DOI: 10.3168/jds.2013-7598
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Circulating and milk adiponectin change differently during energy deficiency at different stages of lactation in dairy cows

Abstract: Adiponectin, one of the most abundant adipokines in circulation, is known for its role in regulation of body metabolism. The aim of this study was to evaluate the effects of a negative energy balance (NEB) at 2 stages of lactation (lactational NEB at the onset of lactation and an induced NEB by feed restriction near 100 d of lactation) on circulating adiponectin concentrations. We also investigated the effect of feed restriction on adiponectin concentrations in milk and the relationships of blood and milk adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 34 publications
6
33
1
Order By: Relevance
“…Those results are in agreement with Sadri et al (2011) who observed decreased leptin concentrations 1 d postpartum compared with values obtained 8 wk prepartum. Singh et al (2014) described that adiponectin concentrations also decreased as a consequence of the onset of lactation; however, in our study adiponectin remained unchanged throughout the entire study period. Possibly, adiponectin concentrations start to decrease several weeks prepartum, as demonstrated by Singh et al (2014), and therefore it was already low at the beginning of our study.…”
Section: Discussioncontrasting
confidence: 65%
“…Those results are in agreement with Sadri et al (2011) who observed decreased leptin concentrations 1 d postpartum compared with values obtained 8 wk prepartum. Singh et al (2014) described that adiponectin concentrations also decreased as a consequence of the onset of lactation; however, in our study adiponectin remained unchanged throughout the entire study period. Possibly, adiponectin concentrations start to decrease several weeks prepartum, as demonstrated by Singh et al (2014), and therefore it was already low at the beginning of our study.…”
Section: Discussioncontrasting
confidence: 65%
“…The presence of adiponectin has been documented for human milk (Martin et al, 2006;Bronskỳ et al, 2012). The concentrations of adiponectin in mature human milk (around 20 ng/mL; Bronskỳ et al, 2012) are far below the ones we recently reported for cow milk (610 ng/mL; Singh et al, 2014b), albeit the blood concentrations are comparable in the 1-to 2-digit μg/mL range in both species (Højlund et al, 2006;Singh et al, 2014a). In view of adiponectin's metabolic functions and of the expression of adiponectin receptor 1 in the small intestine of neonatal mice (Zhou et al, 2005), milk adiponectin may play an important role in infant development, both locally and systemically and may also exert a trajectory effect during later ages (Woo et al, 2012).…”
Section: Introductionmentioning
confidence: 56%
“…The amount of PRL released into the blood during milking was calculated by determining the area under the curve between 0 and 40 min relative to the start of milking, and basal PRL concentration was calculated by averaging the concentrations obtained between −20 and 0 min. The proportion of steady-state PRL secreted via milk, which equals the amount of PRL secreted via milk in 24 h multiplied by 100 and divided by the amount of PRL present in the circulation, was calculated according to Singh et al (2014). Differences were considered statistically significant when P < 0.05 and considered a trend when P < 0.15.…”
Section: Discussionmentioning
confidence: 99%